Chaotic fluctuations in mitochondrial function under oxidative stress. Superoxide dismutatase (SOD2) concentrations of 0.013, 0.016,0.0164, 0.0216733 mM - Kembro, Jackelyn Melissa (2022)
These chaotic time series of mitochondrial dynamics under conditions of oxidative stress are analyzed in detail in Kembro et al. 2018. Mitochondrial chaotic dynamics: Redox-energetic behavior at the edge of stability. Mitochondrial model used was described in the project overview and in detail (Kembro et al. 2013. Biophys J 104(2):332-343; Kembro et al., 2014. Front Physiol 5:257).